ANALYSIS OF SAFETY SYSTEM RELIABILITY KI HADJAR DEWANTARA MAKO KODICLATAL BUILDING TOWARDS FIRE HAZARDS PREVENTION - Dodiek Alfianzi; Ikhwan Syahtaria; Udisubakti Cipto Mulyono; I Made Jiwa Astika (JOURNAL ASRO, 2021)
Designing a fire prevention inspection system in buildings is very necessary, to determine the level of reliability. The fire prevention management system uses the following criteria: precautionary measures and preventive supervision against fire hazards. The assessment of the system design is carried out by means of a questionnaire for respondents who understand / are experts in fire problems, and the application of the system design uses direct surveys and questionnaires to the building manager. The assessment is carried out at the smallest level. Analysis of the building reliability inspection system in fire prevention using the Analytical Hierarchy Process (AHP) method, the criteria used are: prevention, limitation and extinguishing against fire. The fire prevention management system uses the following criteria: precautionary measures and preventive supervision against fire hazards. The results of the reliability inspection of the Ki Hadjar Dewantara Mako Kodiklatal building in Surabaya with a value of 94.06% indicated that the reliability system was in the "Less Reliable" category for fire hazard prevention. Keywords: Inspection, fire prevention, reliability.